Immune checkpoint inhibitor-associated aseptic meningitis: a pharmacovigilance study using the FDA adverse event reporting system (2011–2024) - Guo, Hui; Pang, Yuzhu; Guo, Qian; Wang, Ze; Wang, Haixiong (Frontiers in Immunology, 2025)
ObjectiveImmune checkpoint inhibitors (ICIs) are pivotal in oncology but carry risks of immune-related adverse events (irAEs). Aseptic meningitis (AM) represents a serious neurological irAE, yet real-world evidence on regimen-specific risk variations remains limited. This study aimed to characterize AM reporting patterns and safety signals across ICI regimens using FDA Adverse Event Reporting System (FAERS) data.MethodsWe analyzed FAERS reports (January 2011–December 2024) for ICIs-associated AM. Descriptive statistics summarized demographics, clinical profiles, and temporal trends. Disproportionality analyses employed four algorithms: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS).ResultsAmong 498 ICIs-associated AM reports, monotherapy predominated (78.7%) with pembrolizumab (34.9%), ipilimumab/nivolumab (21.3%), nivolumab (17.1%), and atezolizumab (15.9%) as leading agents. Patients had a median age of 64 years; 98% met serious adverse event criteria. Hospitalization (45.8%) was the most common outcome. Symptom onset was rapid (median: 34 days). Disproportionality analysis revealed pronounced signals for ipilimumab/nivolumab (ROR 5.71, 95% CI 4.71–6.91) and ipilimumab monotherapy (ROR 4.21, 95% CI 3.05–5.82). Anti-PD-1 agents collectively showed moderate association (ROR 2.55, 95% CI 2.25–2.88).ConclusionsICIs-associated AM presents a clinically significant safety concern, particularly with ipilimumab-containing regimens. Rapid symptom onset underscores the need for vigilant neurological monitoring during early treatment phases. These findings warrant integration into clinical risk-assessment protocols and warrant further mechanistic investigation.